On the ambivalence in evaluating the notion represented by the Czech lexeme chytrost - Wójcik, Aleksandra (Papers in Linguistics, 2023)
This article seeks to explain reasons for ambivalence in the evaluation of the notion chytrost, which is understood in Czech primarily as a value, and secondarily as an anti-value. For this purpose, the methods of Lublin ethnolinguistics were used to recreate a stereotype of the notion chytrost in the modern Czech language. In the first part of the article, the stereotype is reconstructed based on systemic data that allow one to determine the semantic content of the lexeme, and in the second part – on the basis of textual data providing information on evaluation. The third part presents the semantic evolution of the lexemes chytrost and chytrý from the Old Czech period to the present day. It shows which elements of the old understanding of the concept have been preserved in the stereotype, contributing to its negative evaluation. The conclusion includes a short cognitive definition of the concept chytrost, which – in contrast with the taxonomic definitions from Czech dictionaries – enables us to distinguish chytrost from other Czech lexemes relating to the mental sphere (e.g. moudrost). The distinction between chytrost as a mental trait and as a character trait allows one also to determine in which contexts chytrost is evaluated positively, and in which – negatively.